2018
DOI: 10.1002/maco.201810317
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electrospun TiO2 nanowires on corrosion resistance and cell response of Ti50Zr alloy

Abstract: TiO2 nanowires are fabricated by electrospinning on Ti50Zr alloy, by changing the elaboration conditions. The surface covered with nanowires is characterized by performing scanning electronic microscopy and contact angle measurements. The best surface from the point of view of nanowires organization is chosen based on experimental conditions. The electrochemical stability is tested in Fusayama saliva. The response of HGF‐1 gingival fibroblasts cells is established and discussed. Cellular response is evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Based on the existing expertise, we chose to present the unmodified and modified surface properties of Ti50Zr [36][37][38] with better biocompatible antibacterial coatings. Drug loading and release from such coatings [39][40][41][42] are discussed as a part of the coated Ti50Zr performance, and future trends in dental materials applications are presented.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the existing expertise, we chose to present the unmodified and modified surface properties of Ti50Zr [36][37][38] with better biocompatible antibacterial coatings. Drug loading and release from such coatings [39][40][41][42] are discussed as a part of the coated Ti50Zr performance, and future trends in dental materials applications are presented.…”
Section: Methodsmentioning
confidence: 99%
“…Ti50Zr surfaces were coated with n-type semiconductor TiO 2 nanowires by electrospinning, improving the surface hydrophilicity and corrosion behaviour without generating significant inflammatory processes [39].…”
Section: Ti50zr Alloy Surface Modificationmentioning
confidence: 99%
“…Alkali-heat treatment and electrospinning have been reported to deposit nanowires on Ti implants, which could be interconnected into nanoscale mesh structures that shield the underlying Ti against chemical corrosion [ 71 , 72 ]. For instance, Zhu et al reported the deposition of nanowires on Ti implants after a sequential acid etching (0.4% HF for 30 min) and alkali-heat treatment (soaking in 10% NaOH for 15 min) [ 71 ].…”
Section: Enhancing Corrosion Resistancementioning
confidence: 99%
“…Chen et al [ 90 ] used induction heating combined with alkali treatment to prepare a stable layered micro-nanoporous network structure on the surface of Ti, resulting in a more uniform coating surface with a higher number of pores, and improved roughness, wettability, and bonding strength with the matrix, as well as significantly improved in vitro and in vivo biocompatibility properties. Manole et al [ 91 , 92 ] deposited n-type semiconducting TiO 2 nanowires onto a Ti-50Zr surface by electrostatic spinning and improved the hydrophilic and corrosion behavior of the alloy surface whilst avoiding significant inflammatory processes. The protection efficiency of the coatings remained greater than 51%.…”
Section: Surface Modification For Biomedical Ti and Ti Alloysmentioning
confidence: 99%